Diagnostic imaging of a Rare Intraosseous Mandibular Schwannoma using Cone Beam Computed Tomography – A case report (Indian Journal of Case Reports, 2020)
Intraosseous schwannoma is a very rare (<1%), slow-growing, benign tumor of Schwann cells. The mandible is the most common site for intraosseous schwannoma. Here, we report the case of a 35-year-old female reported with extraoral and intraoral swelling with bicortical expansion on the left side of the mandible for the past 6 months. Two-dimensional imaging modalities (intraoral periapical radiograph, orthopantomogram, and occlusal radiograph) showed giant well-defined false multilocular radiolucency appearance in the left body of the mandible and external root resorptions of the premolars and molars. Aspiration was non-productive. Cone-beam computed tomography (CBCT) study showed a bicortical expansile unilocular hypodense lesion in continuity with the widened mandibular canal suggesting a tumor of neural tissue origin. Radiological diagnosis of intraosseous schwannoma was given and histopathological examination after an excisional biopsy confirmed the same. The postsurgical phase was uneventful and the patient is under follow-up. This article highlights the importance of three-dimensional modality like CBCT in narrowing the diagnosis of such rare clinically misleading presentations